Perancangan User interface Website BPS Versi Mobile untuk Lansia Menggunakan Pendekatan User Centered Design - Tasya Mina Alifia; Lutfi Rahmatuti Maghfiroh (Politeknik Statistika STIS, 2022)
The rapid development of technology, the number of elderly people in Indonesia which continues to experience an increase as well as the structure of the Indonesian population entering the ageing population requires the Indonesian Government to pay attention so that this phenomenon can be used as a second demographic bonus. The elderly also have many obstacles in the process of self-digitization due to their physical and mental condition. Based on the preliminary survey, all respondents stated that there are several factors of the BPS Website that are not suitable for the elderly so that the current BPS Website tends to make it difficult for elderly users. Therefore, the BPS Website as the main reference website in the world of statistics should have a special user interface for the elderly so that the design of the mobile version of the BPS Website user interface for the elderly is carried out using the User Centered Design method. The conclusion reached that the study stopped at iteration three and was declared complete. The Final Prototype has been produced and designed according to user requirements and has gone through several iteration processes. The output in this study is in the form of guidelines for designing a mobile version of the BPS Website interface for the elderly.